How to Analyze the Potential of Digital Games for Human Rights Education (Revista Lusófona de Educação, 2018)
Serious games that address topics related to human rights education have become increasingly available since the launch of Escape from Woomera in 2003, a game that raises awareness of the plight of refugees. A majority of serious games in the field of human rights focus on topics related to refugees and poverty in order to raise awareness and evoke empathy for the groups depicted. The paper introduces the Serious Games Design Assessment (SGDA) Framework as a tool to find out if a certain game might be used to achieve the objective the designer intended when designing the game. Using the game Bury Me, My Love, which shows the journey of a Syrian woman wanting to escape to Europe, the approach is explained in detail. The conclusion of the game-analysis shows that Bury Me, My Love can be regarded as a successful example of a serious game that introduces and engages the player in what it means to leave your home country as all game-design elements support the purpose.Keywords: human rights; games for change; serious games; game-design; teaching.